2020
DOI: 10.1002/cam4.3663
|View full text |Cite
|
Sign up to set email alerts
|

Association of image‐defined risk factors with clinical features, histopathology, and outcomes in neuroblastoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…More innovative approaches need to be discovered. 17 Therefore, identifying this subpopulation as early as possible would allow us to direct experimental therapies. In our study, 17 cases were considered to be ultra high‐risk among the 146 high‐risk patients, accounting for 11.6%.…”
Section: Discussionmentioning
confidence: 99%
“…More innovative approaches need to be discovered. 17 Therefore, identifying this subpopulation as early as possible would allow us to direct experimental therapies. In our study, 17 cases were considered to be ultra high‐risk among the 146 high‐risk patients, accounting for 11.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have reported cases of successful emergency surgery on the primary mass in patients with ruptured neuroblastoma ( 7 , 13 ); in our case series, all the patients with hemorrhagic complications presented with encasement of the aorta and its major branches, that is a well-documented risk factor for major surgical complications and incomplete resection ( 28 30 ). In this scenario, emergency surgery on the primary mass should be reserved to patients who do not respond to other therapeutic measures.…”
Section: Discussionmentioning
confidence: 74%
“…Neuroblastoma patients with hemorrhagic complications need multimodal treatment that should be focused at controlling and limiting the bleeding while supporting vital functions, consisting in blood products administration, crystalloid and colloid infusion, surgical drain of hemothorax and angiographic control of the bleeding source. Some authors have reported cases of successful emergency surgery on the primary mass in patients with ruptured neuroblastoma (7,13); in our case series, all the patients with hemorrhagic complications presented with encasement of the aorta and its major branches, that is a well-documented risk factor for major surgical complications and incomplete resection (28)(29)(30). In this scenario, emergency surgery on the primary mass should be reserved to patients who do not respond to other therapeutic measures.…”
Section: Discussionmentioning
confidence: 84%
“…Temple and colleagues provided an alternative way to stratify neuroblastoma according to risk with comparison of image-defined risk factors with molecular and histopathologic features. 10 Utilising established databases for the evaluation of these associations may lead to development of clinical strategies. A further translation, based on diagnostic resources available in limited resource settings, can be done.…”
Section: Application Of Expertise Diagnostics and Clinical Acumenmentioning
confidence: 99%
“…Risk stratification during diagnosis has become the benchmark for treatment in childhood malignancies, but often incorporates advanced biological testing in the stratification. Temple and colleagues provided an alternative way to stratify neuroblastoma according to risk with comparison of image‐defined risk factors with molecular and histopathologic features 10 . Utilising established databases for the evaluation of these associations may lead to development of clinical strategies.…”
Section: Application Of Expertise Diagnostics and Clinical Acumenmentioning
confidence: 99%